Penggunaan Snort Sebagai Sistem Pendeteksi Serangan Pada Jaringan Menggunakan Notifikasi Telegram (Kasus Dinas Komunikasi Informatika Dan Persandian Kabupaten Sukabumi) - Fergina, Anggun; Ikhsan, Sultan Alif Nur; Alamsyah, Zaenal (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Network security has become very important to protect individuals, companies, and agencies from threats such as cyberattacks, and data theft. Therefore, understanding the importance of network security is essential. Based on the interview results, there is a server in the Sukabumi District Command Center managed by DISKOMINFOSAN Sukabumi District, the server is used as an application server. The server does not have a network security monitoring system that provides alerts when there is an attempted attack on the server in real time. One way to improve security on the server is to use an Intrusion Detection System (IDS). IDS is a system intended to detect suspicious activity or attacks on the network. One of the main goals of IDS is to provide warnings against security threats that may occur. Snort is one of the open-source IDS tools. Snort was created to identify network attacks and provide realtime alerts to administrators when identifying certain behaviors or attack patterns. In this study the authors used the SPDLC development method. Security Policy Development Life Cycle (SPDLC) is a system development method that focuses on network security. After testing, it can be concluded that snort can be used as an IDS installed on ubuntu server 22.04, with the rules that have been made snort can detect when someone tries port scanning to the server using masscan and can detect ping attacks aimed at the server in real time. With the script that has been created, snort can send alerts to network administrators using telegram in realtime so that these alerts can be followed up immediately.